Risk factors for patellar tendinopathy in basketball and volleyball players: a cross-sectional study - van der Worp, H.; van Ark, W.; Zwerver, J.; van den Akker-Scheek, I. (Scandinavian Journal of Medicine & Science in Sports, 2012)
Patellar tendinopathy (PT) has a multifactorial etiology, and many possible risk factors have been described in the literature. The findings are conflicting, though, and most research has been conducted on elite athletes. The aim of the current study is to determine the risk factors for PT in a large representative sample of basketball and volleyball players. Separate risk factors for men and women, basketball and volleyball players, and athletes with unilateral and bilateral PT were identified. All basketball and volleyball players between ages 18 and 35 from the Dutch Basketball Association and the Dutch Volleyball Association were invited to complete an online questionnaire on knee complaints and risk factors for PT. The logistic regression analyses included 2224 subjects. The risk factors for PT were age, playing at the national level, being male and playing volleyball (compared with playing basketball). The risk factors for men and women were comparable. Among volleyball players, outside hitters and middle blockers/hitters had an increased risk compared with setters. For basketball players, no risk factors could be identified. No differences in the risk factors were found between athletes with unilateral and bilateral PT. These findings should be taken into account for prevention and rehabilitation purposes.